UFO Mythologies: Extraterrestrial Cosmology and Intergalactic Eschatology - Wojcik, Daniel (Traditiones, 2022)
The initial flying saucer mythology that arose in the 1950s and 1960s is characterized by explicitly religious and mystical narratives that describe contact with extraterrestrial savior beings. These beliefs emerged in the Cold War era, in response to widespread fears of nuclear apocalypse. This essay traces the origins and development of the early UFO mythos, and presents case studies of several well-known UFO religious groups, analyzing the mythic aspects of their belief systems with particular focus on apocalyptic and millennialist scenarios.